2021
DOI: 10.1590/rbce.43.e001621
|View full text |Cite
|
Sign up to set email alerts
|

Does physical activity improve adaptive behaviour, fitness, and quality of life of adults with intellectual disability?

Abstract: The effects of a physical activity program on adaptive behaviour, motor proficiency, fitness, and quality of life of 16 adults with intellectual disability (ID) were analysed. Portuguese versions of Adaptive Behavior Scale, Personal Outcomes Scale, Bruininsky-Oseretsky Motor Proficiency Test, and Fullerton scale were applied twice before, after, and one month after the program. Mann-Whitney and Wilcoxon tests were used and Bonferroni manual correction was performed to establish a new p-value. The control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Although, the study by Carbo-Carretéa et al (40) confirmed that physical activity perceptions and individualized support habits are associated with improved quality of life. Diz et al (43) concluded that controls showed a better adaptive profile in most adaptive domains, except for time and numbers, sexual behaviour, and social interaction. This group's scores remained the same over time, while the experimental group's performance improved in most areas.…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…Although, the study by Carbo-Carretéa et al (40) confirmed that physical activity perceptions and individualized support habits are associated with improved quality of life. Diz et al (43) concluded that controls showed a better adaptive profile in most adaptive domains, except for time and numbers, sexual behaviour, and social interaction. This group's scores remained the same over time, while the experimental group's performance improved in most areas.…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…Of the 15 studies included in the systematic review, nine are from Europe (Portugal: [ 15 ]; Spain: [ 17 , 38 , 40 , 42 , 44 ]; United Kingdom: [ 18 ]; Ireland: [ 39 ]; Sweden: [ 41 ]), two are from Asia (Israel: [ 6 , 16 ]); two are from North America (USA: [ 45 , 47 ]), one is from Oceania (Australia: [ 46 ] and one is Eurasian (Turkey: [ 43 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Out of a total of 1026 participants, 995 are people with IDD, while the remaining participants are family members of people with IDD, teachers, technical carers, and association presidents. With regard to the age of the participants, it mostly ranges from 16 to 66 years old [ 15 , 16 , 17 , 18 , 38 , 40 , 41 , 42 , 44 , 46 , 47 ], with only two studies using samples of children and adolescents aged between 4 and 14 [ 43 , 45 ] and one study with participants aged between 46 and 77 [ 6 ]. Only one of the included studies made no reference to the age of the sample [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations